Effects of concomitant obesity and diabetes on the aggressiveness and outcomes of differentiated thyroid cancer patients - YAVUZ, DİLEK (SBEM-SOC BRASIL ENDOCRINOLOGIA & METABOLOGIA, 2021)
Objective: Obesity and diabetes are the risk factors for cancer development including differentiated thyroid cancer (DTC). Contradictory accumulated data indicates the possible negative effects of obesity and hyperglyceamia as a factor for aggressiveness of DTC. The aim of the present study is to investigate the association of high body mass index (BMI) and presence of type 2 diabetes mellitus (T2DM) on the histological aggressiveness and clinical outcomes in DTC patients followed for over 4 years in a single center. Materials and methods: Consequative 526 DTC patients who had undergone total thyroidectomy and/or radioactive iodine (RAI) ablation were reviewed retrospectively. Patients were divided into groups based on their BMI: normal weight, overweight, obese and also were evalauted in 3 groups presence of diabetes, prediabetes and nomoglyceamia. Histological aggressiveness of DTC at the time of diagnosis and clinical response at the time of last clinical visit were reassessed according to the criteria suggested by ATA 2015 guideline. Results: No differences in histopathologic features, risk of recurrence, cumulative dose of RAI ablation and prevalence of 131I avid metastatic disease were demonstrated among the groups both classified according to BMI and hyperglycemia. Mean of 3.4 year follow-up also showed no differences in the clinial repsonse to therapy and percentage of nonthyroid primary cancer in DTC patients. Conclusion: In this retrospective study we demonstrated that obesity and T2DM have no additive effect on DTC aggressiveness and response to therapy. DTC patients with obesity and diabetes can be treated according to present guidelines without requirement for spesific attention. Arch Endocrinol Metab. 2021;65(4):455-61
Keywords: Differantiated thyroid cancer; BMI; obesity; prediabetes; T2DM; metastasis; AARP DIET; RISK